Council kicks off Clean Zone community programme - The Star, (2012)
THE FIRST of a series of Clean Zone Community Programme 2012: Green Township Carnival organised by the Subang jaya Municipal Council (MPSj) kicked off last weekend at Taman Tasik Seri Serdang, Seri Kembangan.